EFEKTIFITAS EDUKASI KESEHATAN TERINTEGRASI PADA PASIEN PRE DAN POST OPERASI PANGGUL : LITERATURE REVIEW: The Effectiveness of Integrated Health Education Among Patient Undergo Pre and Post Hip Surgery: A Literature Review - Anas Khafid; Riri Maria (LPPM STIKES Pemkab Jombang, 2020)
Introduction: Hip fracture is a major problem in the elderly throughout the world. Hip arthroplasty is a procedure when treatment and physical therapy are no longer effective. Health education delivers by health care professionals who less will have an impact on the short and long term both physically and mentally. The purpose of this literature review is to explore the effectiveness of health education among patients who undergo pre and post hip surgery. Method: Literature research conducted on the five largest databases consist of Pubmed, Google Scholar, CINAHL, Medline and PsycINFO using medical subject headings